THE INFLUENCE OF THE DISCOVERY LEARNING MODEL ON THE LEARNING OUTCOMES OF CLASS VII STUDENTS OF BINTANG LANGKAT JUNIOR HIGH SCHOOL - Anggraini, Dini Puji; Syafitri, Anis; Kesumawati, Diah; Purba, Azrina; Haryati; Nasution, Unita Sukma Zuliani (Universitas Negeri Medan, 2024)
Low student learning outcomes are a common problem found in the learning process. Learning models that are not yet varied are one of the causes of low student learning outcomes. This research aims to see the effect of the discovery learning model on the learning outcomes of class VII students at Bintang Langkat Junior High School. This research was carried out at Bintang Langkat Junior High School. The population in this study were all class VII students at Bintang Langkat Junior High School. The sample group was divided into 2 classes, namely the control class and the experimental class. Each class will be given a pretest and posttest. The instrument used was a multiplechoice test instrument with 20 questions. Before testing the hypothesis, the data was tested for normality and homogeneity. From the analysis results it was found that the samples were normally distributed and categorized as homogeneous. Next, a statistical hypothesis test can be carried out using the t test. The results of hypothesis testing with the t test show that H0 is rejected. So it can be interpreted that there is an influence of the use of the discovery learning model on the learning outcomes of Bintang Langkat Junior High School students.